Italian horror cinema - Baschiera, Stefano 1977-; Hunter, Russ 1977- (Edinburgh University Press, 2016)
This collection brings together for the first time a range of contributions aimed at a new understanding of the Italian horror cinema genre
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Keywords: Geschichte; Horror films; Motion pictures, Italian; Horrorfilm; Italien; Aufsatzsammlung